Coexistence of Neonatal Lupus Erythematous and Sturge–Weber Syndrome - Zahra Nikyar; Parvaneh Hatami; Zeinab Aryanian; Kambiz Kamyab Hesari; Azadeh Goodarzi; Anahita Borzouei (Case Reports in Dermatological Medicine)
Neonatal lupus erythematous (NLE) is a rare condition presented by lupus dermatitis shortly after birth or later following sun exposure. Sturge–Weber syndrome (SWS) is also an uncommon congenital condition characterized by extensive capillary malformation and ophthalmic and/or neurologic involvement. Here, we describe the first case of coexistence of NLE and SWS which posed a significant diagnostic challenge to clinicians.